Violencia intrafamiliar y trastornos psicológicos en mujeres violentadas, Cumandá 2016-2018 - Garcés Narváez, Fabián Patricio (2020)
The purpose of this degree project is to analyze how intrafamily violence generates certain psychological disorders in the different women within the Cumandá canton and who have been victims of intrafamily violence, through a collection of data extracted from the psychology area of the Multicompetent Judicial Unit of the Canton Cumandá, with the respective authorizations of the different authorities as the clinical psychologist of the unit. Under this background, this research aims to describe how domestic violence becomes a public health problem deteriorating different areas such as family, social and personal of the different women who have been or are victims of domestic violence in the Cumandá canton belonging to Chimborazo province. Among the results, it was possible to observe the prevalence of different types of violence such as physical, psychological and sexual violence, which tends to generate multiple psychological disorders in them, such as neurotic disorders secondary to stressful and somatomorphic situations, mood disorders or generated disorders for excessive consumption of psychotropic substances.